European Accounting - Amat Oriol; Blake John (Pitman Publishing, 1993)
An introductory treatment of comparative international accounting and financial reporting practices in Europe. Preface, Variations in International Accounting, National and International Sources of Authority, An Overview of Areas of Difference in International Accounting Practice, Belgium, Denmark, France, Germany, Greece, Ireland, Italy, Luxembourg, The Netherlands, Portugal, Spain, Sweden, The United Kingdom, Eastern Europe, International Analysis of Accounts, Author and Subject Index.